2020
DOI: 10.1523/eneuro.0121-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Lemniscal and Non-Lemniscal Sources Control Auditory Responses in the Orbitofrontal Cortex (OFC)

Abstract: Parallel lemniscal and non-lemniscal sources control auditory responses in the orbitofrontal cortex (OFC)

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 85 publications
(113 reference statements)
5
16
1
Order By: Relevance
“…By contrast, only 1 repetition was enough for the initial auditory-evoked response in the mPFC to drop between >50% and >70%, and a second repetition to reach maximum suppression levels (Fig 6E, in black). Similar suppressive dynamics were reported in the orbitofrontal cortex of anesthetized and awake mice [52], in the dorsolateral PFC of alert macaques [53], as well as in human frontal sources [22].…”
Section: The Neuronal Substrate Of Mmn-like Potentials In the Rat Brainsupporting
confidence: 78%
See 3 more Smart Citations
“…By contrast, only 1 repetition was enough for the initial auditory-evoked response in the mPFC to drop between >50% and >70%, and a second repetition to reach maximum suppression levels (Fig 6E, in black). Similar suppressive dynamics were reported in the orbitofrontal cortex of anesthetized and awake mice [52], in the dorsolateral PFC of alert macaques [53], as well as in human frontal sources [22].…”
Section: The Neuronal Substrate Of Mmn-like Potentials In the Rat Brainsupporting
confidence: 78%
“…Hence, the fact that we have been able to record very robust mismatch responses in the rat mPFC during anesthesia further strengthens the link between our data and MMN evidence from human research. Moreover, previous studies of mismatch responses in both the auditory system and the PFC of rodents did not find dramatic differences between anesthetized and awake preparations [39,52,79,80]. Notwithstanding, the use of anesthesia is always a limiting factor that must be minded when comparing these data with those obtained from awake preparations, or when trying to extrapolate possible behavioral implications from the conclusions presented in our study.…”
Section: Limitationssupporting
confidence: 52%
See 2 more Smart Citations
“…It is possible that nonauditory subcortical nuclei such as the hippocampus or the amygdala could compute PEs and then broadcast that signal all over the PFC for further processing and integration. Indeed, a very recent study has demonstrated that the emergence of robust and long-lasting mismatch responses in the mouse orbitofrontal cortex is directly controlled from the nonlemnical MGB through the basolateral amygdala [52]. Therefore, all these auditory and nonauditory subcortical nuclei could be fundamental middle players in the automatic process of deviance detection and PE signaling reflected in the MMN.…”
Section: Subcortical Middle Players Could Relay Pe Signals To the Pfcmentioning
confidence: 99%